Ordered assembly of a functional preinitiation transcription complex, containing vaccinia virus early transcription factor and RNA polymerase, on an immobilized template. - Baldick, C J (1994)
A functional preinitiation transcription complex was formed by incubating vaccinia virus early transcription factor VETF and RAP94+ RNA polymerase with an early promoter template immobilized on paramagnetic particles. A preferred order of assembly, VETF followed by RNA polymerase, was demonstrated by stepwise addition experiments. ATP was unnecessary for preinitiation transcription complex formation, but divalent cations were required specifically for the association of RNA polymerase.